A Tale of Progressive Painless Vision Loss in a 64-Year-Old Man Due to Leber Hereditary Optic Neuropathy. Issue 3 (8th September 2022) - Aung, Moe H.; Volpe, Nicholas J.; Choi, Daniel J.; Stein, Joel M.; Goldstein, Amy; Liu, Grant T.
Abstract: A 64-year-old man presented with painless sequential bilateral vision loss, consistent with optic neuropathy, over the span of months. The significant decline in his visual function was out of proportion to the appearance of the optic nerves (which were not pale) or changes in his retinal nerve fiber layer thickness on optical coherence tomography. Neuroimaging revealed only mild T2 signal abnormality and faint enhancement in the left optic nerve. Extensive workup for potential infectious, metabolic, inflammatory, and ischemic etiologies was unremarkable. Empiric treatment with intravenous steroids did not slow or ameliorate the vision loss. Ultimately, genetic analysis revealed a missense m.11778G>A mutation in mitochondrial MT-ND4 gene, consistent with Leber hereditary optic neuropathy. Initiation of multivitamin supplements and idebenone unfortunately did not result in recovery of vision.